2005
DOI: 10.1109/tip.2005.847284
|View full text |Cite
|
Sign up to set email alerts
|

Anti-collusion forensics of multimedia fingerprinting using orthogonal modulation

Abstract: Abstract-Digital fingerprinting is a method for protecting digital data in which fingerprints that are embedded in multimedia are capable of identifying unauthorized use of digital content. A powerful attack that can be employed to reduce this tracing capability is collusion, where several users combine their copies of the same content to attenuate/remove the original fingerprints. In this paper, we study the collusion resistance of a fingerprinting system employing Gaussian distributed fingerprints and orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 27 publications
1
120
0
Order By: Relevance
“…The gradient attack was proposed in [24], which uses the combination of several basic nonlinear collusion attacks in [23]. The work in [25] evaluated the collusion resistance of multimedia fingerprints as a function of system parameters, including fingerprint length, total number of users, and system requirements.…”
Section: Collusion Attacks and Anticollusion Fingerprint Designmentioning
confidence: 99%
“…The gradient attack was proposed in [24], which uses the combination of several basic nonlinear collusion attacks in [23]. The work in [25] evaluated the collusion resistance of multimedia fingerprints as a function of system parameters, including fingerprint length, total number of users, and system requirements.…”
Section: Collusion Attacks and Anticollusion Fingerprint Designmentioning
confidence: 99%
“…In this paper, we first generate independent vector from Gaussian distribution N (0, σ 2 w ), and then apply Gram-Schmidt orthogonalization to generate orthogonal fingerprints for different users. Multi-user Collusion In this paper, we only consider averaging based collusion because nonlinear collusion can be modelled as averaging collusion with additive noise [7], and all collusion attacks have similar performance with colluded copies of the same quality.…”
Section: Scalable Multimedia Fingerprinting Systemmentioning
confidence: 99%
“…Recent investigation in [4] showed that, under the constraints that the colluded copies under different collusions have the same perceptual quality, the performance of nonlinear collusion attacks is similar to that of the averaging attack. Thus, we only consider the averaging based collusion attacks in this paper.…”
Section: Multimedia Forensic Systemsmentioning
confidence: 99%
“…During collusion, an important issue is the fairness of the attack, i.e., whether all colluders have the same probability of being detected. Most prior work assumed that all colluders keep their agreement to share the risk during collusion and focused on the analysis of collusion strategies and effectiveness [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%